DAMPAK JEJARING KOLABORASI DAN KAPABILITAS INOVASI TERHADAP KINERJA - Mitsha Ranatiwi; Mulyana Mulyana (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
Micro Small and Medium Enterprises (MSMEs) is a sector that has an important role ineconomic development in Indonesia, because in economic growth and employment absorptionalso play a role in the distribution of development results. The purpose of this study was toexamine the effect of collaborative networks and innovation capabilities on the performance ofSMEs Batik in Semarang and Kendal. The population in this study are owners of SMEs Batik inSemarang and Kendal. The sample in this study was taken by using the census method with thenumber of samples of 57 respondents. The data obtained is processed using the help of SPSSsoftware version 16.0 with data analysis using multiple linear regression and t test. The resultsshowed that collaborative networks have a significant effect both on innovation capability andperformance. Furthermore, the results of the study also showed that the innovation capabilityhas a significant effect on the performance.Keywords: collaborative networks, innovation capability, performance